Body mass index and risk of inflammatory bowel disease: A systematic review and dose‐response meta‐analysis of cohort studies of over a million participants. (12th June 2019) - Rahmani, Jamal; Kord‐Varkaneh, Hamed; Hekmatdoost, Azita; Thompson, Jacqueline; Clark, Cain; Salehisahlabadi, Ammar; Day, Andrew S.; Jacobson, Kevan
Summary: The relationship between body mass index (BMI) and risk of inflammatory bowel disease (IBD) is controversial. We performed a dose‐response meta‐analysis to investigate the association between BMI and risk of incident ulcerative colitis (UC) and Crohn's disease (CD) using prospective cohort studies. A systematic search was conducted in MEDLINE/PubMed, SCOPUS, Cochrane, and Web of Science databases from inception to January 2019. DerSimonian and Laird random‐effects model was used to estimate combined hazard ratios (HRs). Overall, 882 articles were screened, and 42 full‐text articles were reviewed for inclusion using the study eligibility criteria. Five studies evaluated the association between BMI and IBD with 1 044 517 participants. Pooled results showed a significant association between participants affected by obesity and risk of CD (HR: 1.42, 95% CI: 1.18‐1.71, I 2 : 0.00). There was a significant nonlinear association between BMI and risk of CD ( P  = .01, coeff = 0.5024). Pooled results did not show any significant association between being underweight and risk of UC (HR: 1.07, 95% CI: 0.96‐1.19, I 2 : 0.00) or CD (HR: 1.11, 95% CI: 0.93‐1.31, I 2 : 12.8). There was no difference in the risk for UC among participants affected by obesity compared with participants categorized as having normal BMI (HR: 0.96, 95% CI: 0.80‐1.14, I 2 : 8.0). This systematic review and meta‐analysis identified significant dose‐response relationship between being affected by obesity, as a risk factor, and incidence of CD.